CRYSTAL FABRIC EVOLUTION IN LAVA FLOWS: RESULTS FROM NUMERICAL SIMULATIONS - Iezzi G.; Ventura G. (My University, 2002)
The analysis of the preferred orientation of crystals (crystal fabric) in magmatic rocks has become a widely used technique for the reconstruction of the flow history. However, little is known about the evolution of the fabric during flow. Here, numerical simulations are used to study the fabric evolution of low-concentration, laminar magmatic flows (e.g. lava flows). The fabric evolution of (a) particle populations with a specified shape (cube, tablet, prism, and transitional shape) and (b) crystal populations from a lava flow is analyzed in different flow geometries (simple shear, hyperbolic and pure shear flows) assuming plane strain. Results show that fabric analysis of the whole crystal population gives little information about flow kinematics, whereas the comparative analyses of crystal sub-populations with different shapes allow us to recognize the flow geometry. Simple shear flow produces oscillating to pseudo-stable fabrics. The fabric strength is lower with respect to that of hyperbolic and pure shear flows and the preferred orientation of crystals does not coincide with the flow direction, except for large strain and specified shapes. Sub-fabrics with opposite sense of shear may also develop, depending on the crystal shape and finite strain. Pure shear and hyperbolic flows show stable to pseudo-stable fabrics. The preferred crystal orientation may or may not coincide with the flow direction according to whether flow is in pure or hyperbolic shear. Results from numerical simulations are comparable with those from experimental models and natural examples. The fabric strength depends on the number of crystals and caution must be used in extrapolating the results beyond the scale of observation. The finite strain in a sample from a lava flow from the Aeolian Islands is determined by the comparative analysis of the calculated and measured fabric parameters (fabric intensity and crystal preferred orientation). Criteria to discriminate among fabrics produced by different flow types are also provided.